Potential of the Flavonoid Quercetin to Prevent and Treat Cancer - Current Status of Research - Jana, Neuwirthová; Břetislav, Gál; Pavel, Smilek; Pavla, Urbánková (Klinicka onkologie, 2018)
Naturally occurring bioactive compounds are promising candidates to prevent and treat cancer. Quercetin is a well-known plant flavonoid that is reported to have anticancer actions in vitro and in vivo. This review focuses on the molecular mechanisms underlying the chemopreventive effect of quercetin and its therapeutic potential in oncology. Quercetin elicits biphasic, hormetic, dose-dependent effects. It acts as an antioxidant and thus elicits chemopreventive effects at low concentrations, but functions as a pro-oxidant and may therefore elicit chemotherapeutic effects at high concentrations. Quercetin has multiple intracellular molecular targets with the potential to reverse treatment resistance and affect pleiotropic signaling processes that are altered in cancer cells. Studies suggest that quercetin binds to several receptors that play important roles in carcinogenesis, regulates expression of various genes, induces epigenetic changes, and interferes with enzymes that metabolize chemical carcinogens. In addition, it also elicits anti-inflammatory and antiviral effects. The ability of quercetin to induce apoptosis of cancer cells without affecting non-cancer cells has been documented using various cell lines. Quercetin also has antiangiogenic and antimetastatic properties. When used in combination with chemotherapy and radiotherapy, quercetin can act as a sensitizer and protect non-cancer cells from the side effects of currently used cancer therapies. The safety and potential usefulness of quercetin for the prevention and treatment of cancer have been documented in both animal experiments and a phase I clinical trial. Current studies are focused on nano-formulations to overcome the low bioavailability of natural quercetin, which limits its clinical use as an antitumor agent. Key words: quercetin - flavonoid - chemoprevention - oxidative stress - apoptosis - antitumor agent - cancer therapy - cancer The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 22. 1. 2018 Accepted: 16. 4. 2018.
Keywords: nádory; protinádorové látky; antioxidancia; Antineoplastic Agents; Animals; Humans; quercetin; lidé; Antioxidants; zvířata; Neoplasms; Quercetin